What Sense Can We Make of the Possibility of Vocational Didactics? An Approach from the Spanish School-Based System Complemented by Non-Formal Vocational Training - Fernando Marhuenda; Alicia Ros-Garrido (European Research Network Vocational Education and Training (VETNET), 2015)
Our contribution attempts to review the development of the field of didactics in Spain in the past 35 years and its contribution to the development and improvement of vocational education and training. We intend to show that the concern of didactics is an issue of great concern (and dispute) in Southern Europe, for which we will use Spain as an example. We will particularly analyse from a didactical approach (taking didactics as a normative applied discipline well established in academia) the possibilities that a traditionally school-based discipline has to improve the development of vocational education practice in and out of schools, for young and adult people, in terms of pedagogical innovation.